Sexual Assault and Cancer Screening Among Men and Women - Alcalá, Héctor E. (Journal of interpersonal violence, 2021)
Emerging research has shown that experiences of sexual violence are associated with cancer screening behaviors. However, to date, little attention has been given to the impact of sexual assault on cancer screening behaviors, particularly among men. To address this, we used data from the 2014 Kansas Behavioral Risk Factor Surveillance System. This survey is conducted annually via telephone. Logistic regressions were used to calculate odds of ever engaging (i.e., lifetime) in specific screening behaviors (clinical breast exam [CBE], mammogram, Pap test, colonoscopy/sigmoidoscopy, fecal occult blood test and prostate-specific antigen [PSA] test) and current compliance with cancer screening recommendations (CBE, mammogram, Pap test, colorectal cancer screening, and PSA test), with lifetime sexual assault as the independent variables. Colorectal cancer screening models were stratified by gender. All models adjusted for confounders. Sexual assault was associated with lower odds of ever receiving a PSA test and, for women, higher odds of ever receiving a colonoscopy or sigmoidoscopy. Sexual assault was associated with lower odds of current compliance with CBE, mammogram, Pap test, and PSA test screening recommendations. A history of sexual assault was associated with lower odds of current compliance with cancer screening procedures, with the notable exception of colorectal cancer screening. Less consistent patterns were seen for lifetime screenings. Results suggest that alternatives to currently recommended procedures (like self-collection of HPV [human papilloma virus] DNA) or modified screening procedures may be a promising route to increase current compliance with cancer screening among a population that may avoid these procedures due to pain or fear of retraumatization.